MENTORING ISLAMIC RELIGIOUS VALUES FOR DROPOUT STUDENTS IN KALIBARU MANIS VILLAGE BANYUWANGI - Haris Sulmiftah; Rosichin Mansur; Moh. Muslim (UIN Sumatera Utara Medan, 2022)
Islamic religious values become a barometer of character education for students. Dropping out of school has a negative impact on a child's development, and has a social impact on society. This study aims to describe the mentoring of Islamic religious values to dropout students, analyze the method of mentoring Islamic religious values, and provide an overview of the inhibiting factors for mentoring Islamic religious values to dropout students. The researchers use a qualitative method with a case study approach. Researchers used in-depth interviews, participant observation, and document study techniques. The results of the study provide an overview of students dropping out of school through non-formal education study groups getting assistance with Islamic religious values ranging from the values of wisdom, honesty, faith, morals, and basic values. Islamic religious values are implemented through mentoring methods including: habituation methods, exemplary, and mau'izah hasanah (good advice). Obstacles during the process of mentoring Islamic religious values to dropout students include: (1) the economic condition of the community below the poverty line; (2) laggard community culture; (3) lack of parental attention to children's education; (4) the unavailability of learning facilities at the junior high school level; and (5) the location of the school which is far from the community's house. So, parents and students dropping out of school have to spend more money, time, and energy to travel to the nearest school. However, the implication that occurs when education access is not available is that more dropout students do not get the 12 year compulsory education service as announced by the government.